2008
DOI: 10.1111/j.1365-294x.2007.03665.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombination and genetic differentiation among natural populations of the ectomycorrhizal mushroom Tricholoma matsutake from southwestern China

Abstract: Effective conservation and utilization strategies for natural biological resources require a clear understanding of the natural populations of the target organisms. Tricholoma matsutake is an ectomycorrhizal mushroom that forms symbiotic associations with plants and plays an important ecological role in natural forest ecosystems in many parts of the world. It is also an economically very important gourmet mushroom. Because no artificial cultivation is available, natural populations of this species are under in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 26 publications
3
38
3
Order By: Relevance
“…Conversely, studies at a larger geographic scale include examples of structure: Bergemann and Miller (2002) found F st values as high as 0.434 in populations of Russula brevipes separated by over 1,500 km, although they raised the possibility that these populations may represent separate cryptic species. Likewise a study of Tricholoma matsutake by Xu et al (2008) found F st values ranging from 0.016 to 0.232 in seventeen populations (which partially overlap this study) separated by \50 km-[1,100 km.…”
Section: Introductionmentioning
confidence: 55%
“…Conversely, studies at a larger geographic scale include examples of structure: Bergemann and Miller (2002) found F st values as high as 0.434 in populations of Russula brevipes separated by over 1,500 km, although they raised the possibility that these populations may represent separate cryptic species. Likewise a study of Tricholoma matsutake by Xu et al (2008) found F st values ranging from 0.016 to 0.232 in seventeen populations (which partially overlap this study) separated by \50 km-[1,100 km.…”
Section: Introductionmentioning
confidence: 55%
“…Right-hand labels indicate signature DNA fragments corresponding to SW (273 bp) and NE (493 and 337 bp) Chinese matsutake samples regions, a large and unsaturated market in Japan, expanding popularity within China, and the shrinking supply of matsutake in Japan, China, and Europe (Arnolds 1991;Wang and Hall 2004;Xu et al 2001Xu et al , 2008. Whether this traceability system is broadly applicable to other matsutake production areas both within and outside Asia remains to be determined.…”
mentioning
confidence: 95%
“…This species is distributed in Europe, North America, and Asia (Xu et al 2001(Xu et al , 2008Chapela and Garbelotto 2004;Murata et al 2008). Matsutake collected from different parts of the world are priced very differently in Japan-the world's preeminent consumer market-from less than US$100 to more than US$4000/kg (Murata et al 2008).…”
mentioning
confidence: 98%
See 2 more Smart Citations